Development of novel paper-based electrochemical device modified with CdSe/CdS magic-sized quantum dots and application for the sensing of dopamine. (20th January 2021) - de França, Caio César Lima; Meneses, Diógenes; Silva, Anielle Christine Almeida; Dantas, Noelio Oliveira; de Abreu, Fabiane Caxico; Petroni, Jacqueline Marques; Lucca, Bruno Gabriel
Highlights: A novel paper electrochemical platform modified with quantum dots is presented. CdSe/CdS magic-sized quantum dots (MSQDs) were used to improve the sensitivity. MSQDs present several advantages in comparison with traditional quantum dots. This is the first report regarding the use of MSQDs for electroanalytical purposes. The modified sensor was successfully applied for dopamine sensing in human serum. Abstract: A novel and disposable electrochemical platform is presented in this work. The paper electrochemical device (PED) developed here consists of a simple and inexpensive three-electrode system drawn over a tracing paper substrate. The graphite working electrode (5 mm diameter) was modified with CdSe/CdS magic-sized quantum dots (MSQDs) to improve the sensitivity. To the best of our knowledge, this is the first full report of the analytical use of MSQDs for modification of electrochemical sensors. This modified electrode was fully characterized and optimized. The best results were obtained when 10 µg MSQDs were deposited over the electrode surface. This proportion provided an amplification of ca . 46% in the peak currents in comparison with the bare electrode, besides decrease the charge transfer resistance and increase the electroactive area of the sensor. Furthermore, the quantum dots-based sensor presented good stability, repeatability and reproducibility (relative standard deviations were ca . 7.2% or less regarding the peak currents). The analytical suitability of this electrochemical platform was demonstrated by detecting dopamine using differential pulse voltammetry. The analyte presented great electrochemical activity over the surface of the modified electrode and the signal showed dependence on the concentration range from 0.5 to 15 µmol L − 1 . The limit of detection achieved (96 nmol L − 1 ) was lower than those stated in other recent reports that use more expensive and complex electrochemical systems. Lastly, the platform was successfully employed for the sensing of dopamine in human blood serum samples with recovery rates between 95.2 and 102.6%. Graphical abstract: Image, graphical abstract